O emprego da eletroestimulação associada à técnica de tubulação na regeneração do nervo ciático de ratos wistar após transecção sem perda de substância - Pitágoras, Tatiana Zotti (2018)
Introduction: Peripheral nerve transection injuries are common and occur frequently in clinical practice and are responsible for serious problems such as pain, loss of sensibility and motor, and permanent sequelae. Great advances were obtained in the treatment of peripheral nerve lesions due to greater knowledge about their physiology and the development of techniques such as microsurgery. The results of electrical stimulation are encouraging and suggest its use as an alternative treatment. Objective: To evaluate, in vivo, the use of electrostimulation (EE) associated with the tubulization technique on the repair of sciatic nerve injury in Wistar rats. Materials and Methods: Ninety male Wistar isogenic rats weighing between 200 and 300 grams were divided into three groups of 30 rats (electrostimulation associated with the tubing technique (EE), tubing suture (ST) and suture(SUT), which were subdivided into three other groups with ten animals according to the evaluation time, with three, six and nine weeks postoperative. Regeneration was assessed by ‘walking track’ analysis and histological analysis in which determination of the area and number of Schwann cells in the nerve samples. Results: In the functional evaluation, the group that received only one EE with 20 Hz, 3 V for one hour presented a superior result, statistically significant when compared to those stimulated more than once, however when comparing the three different types of treatment at the end of the nine weeks there was statistically significant superiority in the treated with standard suture. Regarding the number of cells, no statistically significant result was found in either group. The findings related to the nerve area, in those submitted to EE at three weeks, when compared to the other groups in the same period, were significant, and in the comparison within the same group, those with suture and tube at six weeks obtained a regenerated nerve with area in a statistically significant way.